PENGENDALIAN PERSEDIAAN BAHAN BAKU KEDELAI GUNA KELANCARAN PROSES PRODUKSI PADA PABRIK TAHU HIKMAH MUDA DI KABUPATEN WONOGIRI - Veranita Widya Pangestika; Hendratmoko, Christiawan (Bajang Institute, 2025)
The problem that often occurs in purchasing raw materials is how to stock up on the right raw materials so as not to incur excess costs embedded in the raw materials and not disrupt the smooth production process. This study aims to determine the number or quantity of economic orders, safety stock, reorder point, and total inventory costs as well as to compare the efficiency of inventory management carried out by the Hikmah Muda Tofu Factory with the EOQ model of inventory management. The type of research used is descriptive quantitative where the data used is in the form of numerical data which is then described and analyzed in the form of sentences. The data used is secondary data in the form of inventory reports related to material prices, material inventory quantities, ordering costs and material inventory storage costs for the 2022 period. The data collection methods used are observation, interviews and documentation. The results of this study indicate that the purchase of raw materials implemented by the company is considered inefficient, because it results in a sizable expenditure of Rp. 3,023,070, whereas with the application of the EOQ method, Hikmah Muda Tofu Factory incurs costs of Rp. 1,609,960.01. By applying the EOQ method you can save costs of Rp 1,413,109.99. These cost savings are obtained from minimizing the total cost of inventory, whereby using the EOQ method will optimize the quantity of purchases to be greater and the frequency of orders to be lower than the policy applied, resulting in savings in ordering costs. The results of this study indicate that the application of the EOQ (Economic Order Quantity) method at the Hikmah Muda Factory is more efficient than using company policy.